Large traumatic bone cyst masquerading as an odontogenic keratocyst - Lestari, Marzella M.; Juanda, Dwi N. (Journal of Dentistry Indonesia, 2018)
Traumatic bone cyst (TBC) is a jaw disorder that is asymptomatic, slow growing, and usually detected during routine panoramic examinations. The etiology and pathogenesis of TBC are still unknown. The lack of information and scarce research efforts on TBC has made it difficult for operators to appropriately diagnose and monitor cases, which often requires extensive treatment. Here, we report the case of a moderate-sized TBC, scalloping and pass¬ing through the mandibular midline and suspected to be a malignant lesion.